2015
DOI: 10.1007/s00296-014-3205-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of AA amyloidosis in familial Mediterranean fever

Abstract: The aim of the study was to evaluate the clinical and genetic predictors of AA amyloidosis in patients with familial Mediterranean fever (FMF). We retrospectively studied 170 Armenian patients who were admitted to the two tertiary centers in 2003-2014. The diagnosis of amyloidosis that was suspected clinically (new proteinuria or nephrotic syndrome) was confirmed histologically. Screening for MEFV gene mutations was performed in 70 patients. The most common genotype was M694V/M694V (in 36 % of patients). Biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 16 publications
1
21
0
7
Order By: Relevance
“…This has been reported in a child as young as 5 years of age [24]. This has been reported in a child as young as 5 years of age [24].…”
Section: Amyloidosismentioning
confidence: 63%
“…This has been reported in a child as young as 5 years of age [24]. This has been reported in a child as young as 5 years of age [24].…”
Section: Amyloidosismentioning
confidence: 63%
“…75 Particularly, the M694I/M694I genotype, identified in 52% patients, was significantly associated with the development of amyloidosis in Algerians and Arabs. 68 Authors also described a relationship between the M694I mutation and a higher prevalence of serositis and familial aggregation in Japanese patients with FMF. 76 M680I has been associated with a more severe disease activity, including development of renal amyloidosis.…”
Section: Clinical Phenotype and Gene Variants In Exon 10mentioning
confidence: 98%
“…65 Particularly, unexpectedly though, despite the fact that it has been observed only in the patients with amyloidosis, studies did not link the M694V/M694V genotype to the renal complication. [66][67][68] Moreover, other authors noted that, in southeast Turkey population, the M694V mutation frequency was lower, and disease severity was relatively mild in FMF patients. 16 In addition, any significant association with M694V mutations and pro-inflammatory cytokine as well as markers of oxidative stress was detected in patients with FMF.…”
Section: Clinical Phenotype and Gene Variants In Exon 10mentioning
confidence: 99%
“…20 Another study from Armenia revealed similar results in adults with typical FMF symptoms, and only 9% of patients with amyloidosis were found to be heterozygous for the Met694Val mutation in MEFV. 22 Renal amyloidosis can also be an initial presentation in ∼7% to 25% of patients with FMF, without typical symptoms. This condition is named phenotype II, which is extremely rare in childhood.…”
Section: Figurementioning
confidence: 99%